Dietary apparent metabolizable energy and crude protein levels influence slaughter performance, meat quality, and amino acid composition in slow-growing Danzhou chicken meat - Wang, Dingfa; Zhou, Luli; Shi, Liguang; Cao, Ting; Abouelezz, Khaled; Hou, Guanyu (Frontiers in Animal Science, 2025)
Dietary nutrient composition is an important factor influencing the ultimate properties of poultry carcass and meat quality. This study investigated the effects of varying dietary apparent metabolizable energy (ME) and crude protein (CP) levels on the slaughter performance, meat quality, and amino acid profiles in native Danzhou chickens aged from 120 to 150 days. A total of 720 120-day-old female Danzhou chickens were randomly assigned to six experimental diets with two ME levels (11.70 and 12.50 MJ/kg ME) and three CP levels (13, 14 and 15% CP). The results showed that dietary ME and its interaction with CP had a significant impact on the semi-eviscerated carcass percentage and eviscerated carcass percentage of the chickens (P < 0.05). Irrespective of ME level, the dietary 14% CP reduced (P < 0.05) the drip loss and shear force of thigh muscle than those in the 15% CP group, increased (P < 0.05) the intramuscular fat (IMF) content in both breast and thigh muscles compared to 13% CP, and enhanced (P < 0.05) L-arginine and L-ornithine levels in breast muscle relative to both 13% and 15% CP groups. A significant interaction between dietary ME and CP levels were observed for L-threonine and L-proline content in the breast muscle, as well as for L-glutamic acid in the thigh muscle (P < 0.05). In summary, a dietary metabolizable energy level of 12.50 MJ/kg paired with a 14% crude protein content can enhance the slaughter performance and meat quality in native growing Danzhou chickens. Appropriate dietary energy and protein levels will provide a scientific support for the precise formulation of diets for Danzhou chickens in the future.